Intimate Partner Violence in African Immigrant Communities in the United States: Reflections from the IDVAAC African Women's Round Table on Domestic Violence. Issue 1 (2nd January 2016) - Mose, Grace B.; Gillum, Tameka L.
ABSTRACT: African women face many challenges when they come to the United States due to the immigration experience, acculturation, and leaving family members in countries of origin. Intimate partner violence (IPV) complicates African women's experience within their home countries as well as in the United States. There is little literature on IPV in African ethnic groups. This information is even sparser regarding IPV among African immigrant and refugee communities in the United States. To better address the needs of these communities, the Institute on Domestic Violence in the African American Community brought together service providers and survivors representing 16 different African countries to attend a roundtable and explore issues of IPV. This article highlights the unique challenges they identified.